First report of Comamonas kerstersii causing urinary tract infection. (July 2018) - Almuzara, M.; Cittadini, R.; Estraviz, M.L.; Ellis, A.; Vay, C.
Abstract: The association of Comamonas kerstersii with peritonitis resulting from perforated appendix and its isolation from a psoas abscess and pelvic peritonitis have previously been described by us. We present the first case of C. kerstersii urinary tract infection, broadening the spectrum of infections caused by this species.